Use of social health insurance for hospital care by internal migrants in China—Evidence from the 2018 China migrants dynamic survey - Yao, Qiang; Li, Hanxuan; Liu, Chaojie (Frontiers in Public Health, 2022)
Background: China’s welfare system including social health insurance has been closely linked to its unique household registration system, despite high population mobility over the past few decades. This study aimed to determine the pattern of health insurance usage from the internal migrants in mainland China for hospital care. Method: Data were extracted from the 2018 China Migrants Dynamic Survey. The respondents who enrolled in a social health insurance program and reported illness or injury over the past year were eligible for this study (n=15,302). Two groups of outcome indicators were calculated assessing the use (incidence and settlement location) of insurance funds for hospital care and the burden of hospital expenditure (total hospital expenditure, out-of-pocket payments, and share of insurance reimbursement), respectively. Logit regression and Heckman’s sample selection models were established to determine the predictors of insurance fund usage and burden of hospital expenditure, respectively. Results: Most respondents enrolled in a social health insurance program outside of their residential location (70.72%). About 28.90% were admitted to a hospital over the past year. Of those hospitalised, 72.98% were admitted to a hospital at their migration destination, and 69.96% obtained reimbursement from health insurance, covering on average 47% of total hospital expenditure. Those who had a local insurance fund aligned with residency (AOR=2.642, 95% CI=2.108-3.310, p<0.001) and enrolled in the employment-based insurance (AOR=1.761, 95% CI=1.348-2.301, p<0.001) were more likely to use insurance funds for hospital care, and paid less out-of-pocket (β=-0.183 for local funds, p=0.017; β=-0.171 for employment-based insurance, p=0.005) than others. A higher share of insurance reimbursement as a proportion of hospital expenditure was found in the employment-based insurance enrollees (β=0.147, p<0.001). Insurance claim settlement at the residential location was associated with lower total hospital expenditure (β=-0.126, p=0.012) and out-of-pocket payments (β=-0.262, p<0.001), and higher share of insurance reimbursement (β=0.066, p<0.001) for hospital expenditure. Conclusion: Low levels of health insurance benefit for hospital care are evident for internal migrants in mainland China, which are associated with the funding arrangements linked to household registration and inequality across different funds.